2013
DOI: 10.1016/j.sleep.2012.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Increased cortical excitability after selective REM sleep deprivation in healthy humans: A transcranial magnetic stimulation study

Abstract: a b s t r a c tBackground: REM sleep has antiepileptogenic properties whereas, its loss is known to have a proconvulsive role. However, the mechanisms underlying the proepileptogenic effects of REM sleep deprivation are yet not fully understood. The aim of our study was to evaluate the effects of selective REM sleep deprivation (SRD) on cortical excitability in healthy subjects by means of transcranial magnetic stimulation (TMS). Methods: Ten normal subjects underwent three TMS sessions: (1) in baseline condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 46 publications
4
26
1
Order By: Relevance
“…Moreover, recently, the hypercortical excitability of sleepdeprived healthy subjects, particularly when selectively deprived of rapid eye movement sleep, was demonstrated by using transcranial magnetic stimulation (Huber et al, 2013;Placidi et al, 2013). Here, we were able to demonstrate that the hyperexcitability of IEA is related to deviations from critical dynamics, thus providing additional support to the association between critical dynamics and EIB (Shew et al, 2009;Poil et al, 2012).…”
Section: Neuronal Avalanches In Epilepsy: Integration Into the State supporting
confidence: 73%
“…Moreover, recently, the hypercortical excitability of sleepdeprived healthy subjects, particularly when selectively deprived of rapid eye movement sleep, was demonstrated by using transcranial magnetic stimulation (Huber et al, 2013;Placidi et al, 2013). Here, we were able to demonstrate that the hyperexcitability of IEA is related to deviations from critical dynamics, thus providing additional support to the association between critical dynamics and EIB (Shew et al, 2009;Poil et al, 2012).…”
Section: Neuronal Avalanches In Epilepsy: Integration Into the State supporting
confidence: 73%
“…Some studies report heightened cortical excitability when assessed during wakefulness or after REM sleep deprivation (relative to undisturbed sleep) [22, 23] whereas other studies reported no state-dependent changes in cortical excitability. In two separate studies [24, 25], cortical excitability and intracortical inhibition were measured at different times of day, after periods of sleep or wake, or after sleep deprivation.…”
Section: Changes In Synaptic Efficacy Across the Sleep-wake Cyclementioning
confidence: 99%
“…Only a trend toward an increased cortical excitability was instead observed in healthy controls (Del Felice et al, 2011). Unfortunately, many conflicting views emerge when the studies on the influence of SD on TMS parameters in healthy controls are considered (Civardi et al, 2001;De Gennaro et al, 2007;Huber et al, 2013;Kreuzer et al, 2011;Manganotti et al, 2001;Placidi et al, 2013;Scalise et al, 2006).…”
Section: Experimental Studies On the Effects Of Sd On Cortical Excitamentioning
confidence: 99%